[(x+2y)(x-2y)+4(x-y)²]÷6x
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 01:37:50
[(x+2y)(x-2y)+4(x-y)²]÷6x[(x+2y)(x-2y)+4(x-y)²]÷6x[(x+2y)(x-2y)+4(x-y)²]÷6x[(x+2y)(x-
[(x+2y)(x-2y)+4(x-y)²]÷6x
[(x+2y)(x-2y)+4(x-y)²]÷6x
[(x+2y)(x-2y)+4(x-y)²]÷6x
[(x+2y)(x-2y)+4(x-y)²]÷6x
=(x^2-4y^2+4(x^2-2xy+y^2)÷6x
=(x^2-4y^2+4x^2-8xy+4y^2)÷6x
=(5x^2-8xy-)÷6x
=5/6·x-4/3·y
=(x²-4y²+4x²+4y²+8xy]÷6x
=5x/6+4/3*x*y
[x^2-4y^2+4x^2-8xy+4y^2]÷6x
=[5x^2-8xy]÷6x
=[5x-8y]/6
计算:(1)2/(x+y)+4y/x²-y²(2)x²/x+y-x+y
已知x-y=1,y≠0,求{(x+2y)²+(2x+y)(x+4y)-3(x+y)(x-y)}÷y的值.
化简((X-2Y)的平方+(X-Y)(x+Y)-2(X-3Y)(X-Y))除以Y
把6x(x-y)的平方+3(y-x)的立方分解因式我知道答案是6x(x-y)^2+3(y-x)^3=6x(x-y)^2-3(x-y)^3=3(x-y)^2[2x-(x-y)]=3(x-y)^2(x+y)可为什么=6x(x-y)^2-3(x-y)^3=3(x-y)^2[2x-(x-y)]
因式分解x²(x-2y)+y²(2y-x)
x(x-y)-y(y-x)+(x-y)²因式分解
[(x+2y)(x-2y)+4(x-y)²]÷6x
因式分解4(x-y)^2-12(y-x)+y
把(x+y),(x-y)个作为一个整体合并同类项1,7(x+y)-2(x+y)-4(x+y)+2(x+y)2,(x-y)²+2(x-y)-(x-y)-2(x-y)²
1/2x-(x+y/2x -x-y)÷(x+y)
1.(-2a)³·b²÷(8a³b²) 2.-5x(2x²-3x+4)+4x³+15x3.(x²-2y²)(x+2y)-2xy(x-y)4.(x-y+z)(x-y-z)化简求值 [(x+y)(x-y)-(x+y)²-2y(x-2y)]÷(-2y),其中x=5,y=2003
(2x-y)乘(2x+y)+(2x-y)乘(y-4x)+2y(y-3x)
已知x+y=-2,试计算1/2(x+y)+4(x-y)-3(x-y)-3/2(x+y)-x+y的值
若x+y=4,则多项式½(x+y)+4﹙x-y)-3(x-y)-3/2(x+y)-x+y是多少?
(x+y)(x+y)-4(x+y-1)
x(x+y)-y(3x-4y)因式分解.快.
(x-y)(x-y)2(y-x) (x+2y-?)(x-2y+?)
[X+Y]的平方-Y〔2X+Y)-8X〕除以2X